The Garden of Evaluation Approaches Visualization - Montrosse-Moorhead, Bianca; Schröter, Daniela; Becho, Lyssa Wilson (Journal of MultiDisciplinary Evaluation, 2024)
Background: The Garden of Evaluation Approaches (Montrosse-Moorhead, e t al., 2024a) maps evaluation approaches against eight dimensions of p ractice and situates them in their philosophical orientations and meth odological dispositions. Purpose: The Garden’s guiding question is: Ho w do evaluation approaches compare in terms of dimensions that facilit ate use and application? Primary intended users are evaluation practit ioners, and secondary intended users include ecosystem actors (e.g., c lients, program participants, funders), educators, researchers, and th eoreticians. Setting: Not applicable. Intervention: Not applicable. Re search Design: Exploratory sequential mixed methods. Data Collection a nd Analysis: Data collection and analysis included locating and readin g primary sources for each evaluation approach. One team member themat ically coded each source for evidence of an approach’s stance on the e ight dimensions of practice, its’ philosophical orientation and method ological disposition, and steps for implementing the approach in pract ice. This qualitative evidence was used to generate ordinal ratings fo r the eight dimensions using a rating scale developed by the team, and to classify the approaches' philosophical orientation and methodologi cal disposition. Drafts of handouts summarizing qualitative and quanti tative data were reviewed by the two other team members, with dialogue and deliberation among all members used to come to consensus. Finding s: The first iteration of the Garden includes seven approaches: fourth generation evaluation, made in Africa, nation-to-nation evaluation, p ractical participatory evaluation, sistematización de experiencias, th eory-driven evaluation, and transformative participatory evaluation. E ach approach is represented as a flower within the Garden, with each p etal corresponding to the approaches’ stance on one of the eight dimen sions of practice. The colors of the flowers represent the underlying philosophical foundation of the approach. The pattern within the centr al disc of each flower represents the methodological disposition encou raged by the approach. Summaries of the empirical mixed-method analysi s are made transparent in supporting handouts. Future work will grow f lowers for additional approaches and continue to map out the Garden.
Keywords: approach; evaluation practice; model; special issue; theory; visualizing evaluation theory